Belarus : Chernobyl Review - World Bank (Washington, DC, 2013)
The world's worst nuclear accident occurred in Chernobyl on April 26, 1986, releasing at least 100 times as much radiation as the atomic bombs dropped on Hiroshima and Nagasaki. The most affected country was Belarus, for which the environmental, health, and other consequences of the Chernobyl accident were disastrous. The present report reveals that notable differences exist between zones with relatively mild levels of contamination and those with higher levels; contaminated areas suffer from a distorted demographic structure; and the affected territories are mostly agricultural, and tend to be poorer than urban areas; the potential for economic activity is rather limited; the incidence of thyroid cancer in children has increased as a result of radiation exposure; it is difficult to separate the direct impact of radiation from the indirect impact that comes form psychological perceptions of risk, the consequneces of the economy, and the quality of health services; people are ambivalent about the effectiveness of government programs; and sufficient information is not reaching large groups of the population and the information disseminated is not trusted. The four chapters of the report discuss the current situation in the contaminated districts, the fiscal implications and the government's institutional arrangements, the government programs designed to mitigate the consequences, and recommendations for developing improved approaches that would lower the fiscal burden.